2017
DOI: 10.1108/ijppm-11-2015-0167
|View full text |Cite
|
Sign up to set email alerts
|

Implementing the balanced scorecard in a local government sport organization

Abstract: Purpose The purpose of this paper is to examine the issue of performance management in the public sector and specifically the implementation of the balanced scorecard (BSC) methodology on a public (municipal) non-profit sport organization in Greece. The research provides a discussion on the BSC development process, the goals set on each pillar and the outcome that the organization achieved, in order to be used as a roadmap for other managers in the public sector. Design/methodology/approach The study used in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 40 publications
2
24
0
3
Order By: Relevance
“…This result indicates that managers of these organizations are more concerned about allocation of appropriate resources to successfully implement the BSC. This finding is consistent with the findings of Dimitropoulos et al (2017) where they say that 'the human resources are the most significant determinant in the application of a performance-based management methodology'. Table 3 illustrates the results of one sample t-test conducted for perceived strategies.…”
Section: Mean Analysis Of Perceived Strategiessupporting
confidence: 91%
See 2 more Smart Citations
“…This result indicates that managers of these organizations are more concerned about allocation of appropriate resources to successfully implement the BSC. This finding is consistent with the findings of Dimitropoulos et al (2017) where they say that 'the human resources are the most significant determinant in the application of a performance-based management methodology'. Table 3 illustrates the results of one sample t-test conducted for perceived strategies.…”
Section: Mean Analysis Of Perceived Strategiessupporting
confidence: 91%
“…The study also revealed certain barriers to the implementation of a successful balanced scorecard, in particular using a substitute performance measurement tool, the size of the organization, the unavailability of the resources to generate information required to support the BSC method, the lack of time and commitment towards the implementation process and finally the lack of top management support in the design and implementation of the tool. Dimitropoulos, et al (2017) confirms the above and states that a public-sector organization operates under tight budget constraints, as well as scarce economic resources. There are many stakeholders for such an organization and thus required to ensure all varying stakeholder needs are met while the required level of service quality is also maintained.…”
supporting
confidence: 72%
See 1 more Smart Citation
“…This method has been considered by many researchers for different sectors. For example, Dimitropoulos et al [60], Yao and Liu [61] and Ndevu and Muller [62] used this method to assess the effectiveness of governments. Similarly, Ge [63] and Wang et al [64] focused on how to improve the performance of local governments by taking BSC method into consideration.Ćwiklicki [65] conducted this study for non-profit organizations.…”
Section: Literature Review On Balance Scorecard Approachmentioning
confidence: 99%
“…A few of the studies conducted in the field of sports organizations are given in the following. Rodríguez Bolívar, López Hernández and Ortiz Rodríguez (2010); Walmsley (2012) and Dimitropoulos, Kosmas and Douvis (2017) were among the researchers who introduced new applied research into the implementation of a balanced scorecard assessment methodology in sports organizations (4)(5)(6). However, their method pertained to internal assessment.…”
Section: Introductionmentioning
confidence: 99%